2010
DOI: 10.5006/1.3452397
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Epoxy-Coated Rebar in Marine Bridges—Part 1: A 30-Year Perspective

Abstract: The corrosion performance over a nearly 30-year service period of epoxy-coated rebar (ECR) in Florida marine bridges is presented. Severe ECR corrosion was noted earlier in several of those bridges, built with relatively high permeability concrete. Corrosion development took place later in some other structures with less permeable concrete, with instances where the corrosion was associated with preexisting cracks. Corrosion was found to be associated with coating imperfections and coating disbondment. Laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In addition, field surveys on corrosion performance of RC members constructed with epoxy-coated reinforcing bars were also investigated [11][12][13][14][15][16][17][18][19][20][21][22]. Although the first evidence of unsatisfactory field performance of epoxy-coated bars emerged in 1986 in bridges of the Florida Keys [12], many field investigations reported good performance of the epoxy-coated bars.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, field surveys on corrosion performance of RC members constructed with epoxy-coated reinforcing bars were also investigated [11][12][13][14][15][16][17][18][19][20][21][22]. Although the first evidence of unsatisfactory field performance of epoxy-coated bars emerged in 1986 in bridges of the Florida Keys [12], many field investigations reported good performance of the epoxy-coated bars.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that epoxy coatings are is very sensitive to damage during handling and transportation (Manning 1996;Sagüés et al 2010). A report described the setup of bolt corrosion research in the Oslofjord tunnel (Klemetsrud 2016), which considered painted galvanized steel bolts, observed unintended scratches and impurities in the epoxy coating after normal handling and before the test started.…”
Section: Some Experience With the Duplex Protection Systemmentioning
confidence: 99%
“…However, the effectiveness of epoxy-coated rebar as a corrosion control method in reinforced concrete exposed to marine environment is still a controversial condition (Mao et al 2018, Sagues et al 1994. The long-term observation of epoxy coated rebar in marine bridges conducted in USA, illustrated a serious durability problem, and even pushed the forbidden of epoxy coated rebar applied in marine structures (Kessler et al 2001, Sagues et al 2010, Sagues et al 1996). However, the other studies revealed that the epoxy coated rebar could still be used as an alternate to steel after the coating was modified (Rahman, et al 2022).…”
Section: Introductionmentioning
confidence: 99%